CENTRUM Católica's Working Paper Series 2012
DOI: 10.7835/ccwp-2012-09-0010
|View full text |Cite
|
Sign up to set email alerts
|

Culture and Innovation in Peru from a Management Perspective

Abstract: Political stability, macro-economic caution, and the aggress ive pursuit of free trade have enabled Peru to emerge as one of the fastest growing economies in Latin America. This economic expansion has created heightened interest in the evolution of corporate culture and its influence on firm performance. This paper examines organizational performance in relation to the influence of cultural values on innovation by means of a survey of upper level managers . Analysis of the survey results indicates that there w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
(25 reference statements)
1
4
0
1
Order By: Relevance
“…It is also expected from the employees, including the managerial staff, that this person initiates the necessary steps and measures to make sure the company will survive. This finding confirms the tendency of Peruvian firms to be rather hierarchical which is in line with previous findings (Scott and Chaston, 2013; Hofstede Insights, 2020). Such a situation is likely to increase the danger that when the leadership is not convinced about the benefit of a certain approach or measure it will not be implemented and by doing so putting the entire company at risk.…”
Section: Discussionsupporting
confidence: 93%
“…It is also expected from the employees, including the managerial staff, that this person initiates the necessary steps and measures to make sure the company will survive. This finding confirms the tendency of Peruvian firms to be rather hierarchical which is in line with previous findings (Scott and Chaston, 2013; Hofstede Insights, 2020). Such a situation is likely to increase the danger that when the leadership is not convinced about the benefit of a certain approach or measure it will not be implemented and by doing so putting the entire company at risk.…”
Section: Discussionsupporting
confidence: 93%
“…Hace quince años, la economía peruana mostró un crecimiento sostenido (Scott & Chaston, 2012), que la convirtió en una de las economías de mayor crecimiento en la región. Sin embargo, después de la crisis de los commodities (Brenes et al, 2016) se obligó a las empresas a enfrentar un cambio de realidad.…”
Section: Contextounclassified
“…According to Shane (1992), inventions patent and individualism are positive correlated. So, it is believed that individuals who are with high individualism want to perform greater values, and during this process, they might ask the inner group members to form the group agreement and cohesiveness (Scott & Chaston, 2012). Also, this cohesiveness may improve their spirit of cooperation or team work which would motivate their collectivism.…”
Section: The Dynamics Of Open Innovation Between Individualism and Comentioning
confidence: 99%
“…It has been suggested that successful innovation requires specific antecedents with culture being an important determinant (Scott & Chaston, 2012; Ulijn & Weggeman, 2001; Westwood & Low, 2003). Thus, individualism-collectivism as a cultural dimension is thought to affect at the successful open innovation of enterprises like Figure 1.…”
Section: The Dynamics Of Open Innovation Between Individualism and Comentioning
confidence: 99%